The Escuela Graduada Model. Similarities with the current educational model in Spain (2018)
The situation of the Spanish educational system at the end of the 19th century led to the need to modernize the models in force at that time. In this context, a new educational approach emerge in the country, the Escuela Graduada. This model provides new techniques, structures and innovative methods to mitigate the lagging position of education in Spain compared to other European countries. First of all, there was a need to open up to all social levels, since at that time education was limited only to the most privileged sectors. We intend to offer a general view about the implications of the introduction of this model and what it meant for the Spanish school system during the first third of the last century. The opposition of some teaching sectors and the struggle with the Unitarian School allow us to contrast both models. We analyzed the most important aspects of the Escuela Graduada model, from which arose a new educational approach that could only be carried out with a modern school adapted to the circumstances of the time. In addition, we compared it with the current educational model, in order to verify the validity of those improvements.